Program Sosialisasi Halal dan Thayyib dari Pendekatan Psikologi dan Islam bagi Pelaku UMKM di Kecamatan Cempaka Putih Jakarta Pusat - Karimulloh; Caninsti, Riselligia; Nursanti, Ade; Suseno, Dedy; Pendrianto (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
For Muslims, halal and thayyiban in food and drink is an obligation. The importance of understanding for UMKM (Micro, Small and Medium Enterprises) regarding the use of halal raw materials in making food products must be increased, so that these business actors only make halal and thayyib food. Based on Law of the Republic of Indonesia Number 33 of 2014 concerning Halal Product Guarantees, every food, drink and even medicine product circulating in Indonesia is required to have a Halal Certificate. The importance of understanding the selection of halal raw materials and thayyib is an important support in the halal product certification process. Halal and thayyib socialization program from a psychological and Islamic approach aims to increase the knowledge of micro, small and medium enterprises. Then, they can register their products to obtain a Halal Certificate. Halal certificate is one of criteria for the public to consume food and drinks, so that the general public does not worry about the food or drinks they consume. The target of this program is JP42 and Optima Food Court YARSI business owner in Central Jakarta. The program was implemented on Wednesday - Thursday, 24-25 January 2024. The result on pre-test and post-test  were processed using JASP Wilcoxon Signed Rank Test. Based on statistical analysis, the results showed a significant increase in participants’ understanding oh halal and thayyib raw materials, how to process them, and how to obtain them. With this increase in knowledge, it is hoped that business actors can register their business products to obtain a Halal Certificate.